NGC 1275: An Outlier of the Black Hole-Host Scaling Relations - Sani, Eleonora; Ricci, Federica; La Franca, Fabio; Bianchi, Stefano; Bongiorno, Angela; Brusa, Marcella; Marconi, Alessandro; Onori, Francesca; Shankar, Francesco; Vignali, Cristian (Frontiers in Astronomy and Space Sciences, 2018)
The active galaxy NGC~1275 lies at the center of the Perseus cluster of galaxies, being an archetypal BH-galaxy system that is supposed to fit well with the M$_{BH}$-host scaling relations obtained for quiescent galaxies. Since it harbours an obscured AGN, only recently our group has been able to estimate its black hole mass. \\ Here our aim is to pinpoint NGC~1275 on the less dispersed scaling relations, namely the M$_{BH}$-$\sigma_\star$ and $M_{BH}-L_{bul}$ planes. Starting from our previous work \citep{ricci17b}, we estimate that NGC~1275 falls well outside the intrinsic dispersion of the M$_{BH}$-$\sigma_\star$ plane being $~1.2$~dex (in black hole mass) displaced with respect to the scaling relations. We then perform a 2D morphological decomposition analysis on Spitzer/IRAC images at $3.6~\mu$m and find that, beyond the bright compact nucleus that dominates the central emission, NGC~1275 follows a de Vaucouleurs profile with no sign of significant star formation nor clear merger remnants. Nonetheless, its displacement on the $M_{BH}-L_{bul,3.6}$ plane with respect to the scaling relation is as high as observed in the M$_{BH}$-$\sigma_\star$. \\ We explore various scenarios to interpret such behaviors, of which the most realistic one is the evolutionary pattern followed by NGC~1275 to approach the scaling relation. We indeed speculate that NGC~1275 might be a specimen for those galaxies in which the black holes adjusted to its host.